(3GdMeGjI GdLfGFjI dHWGbGJ GdEFJeGf (B:s (3LQGFe HWGbGJ GdOaY GdEdcJQhfj (B/s - (3YHO GdMce, SGeM eMeOs ((3GdbGgQI(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2003)
(3eGgjI HWGbGJ GdEFJeGf,GdLhGfH GdehVhYjI ddMeGjI GdLfGFjI dHWGbGJ GdEFJeGf,LQGFe GdEMJjGd aj GSJNOGe GdHWGbI ef bHd GdMGed GdTQYj dgG,LQGFe GdEMJjGd aj GSJNOGe GdHWGbI ef bHd GdZjQ,GdLhGfH GdELQGFjI habG dJWhQ CSGdjH GdJdGYH aj LQGFe HWGbGJ GdEFJeGf,GdJZdH Ydi GTcGdjI GdEKHGJ GdfGLeI Yf GSJNOGe HWGbGJ GdEFJeGf,ChLg ecGaMI LQGFe HWGbGJ GdEFJeGfs
(3HHdjhZQGajG (B:(3U(B.146s
Keywords: (3GdHfhcs; (3LQGFe GdGehGds